PENGARUH STRATEGI PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR SISWA - Marwah; Nirma Situmorang (Yayasan Baitul Hikmah al-Zain, 2025)
The background to this research starts from the assumption that in maximizing student learning outcomes it is deemed necessary to introduce new innovations in a learning process This research aims to determine the effect of inquiry strategies in improving students’ cognitive learning outcomes. The research uses normative library research, namely by carrying out searches of library materials in the form of literature and legislation related to inquiry learning strategies. This research aims to determine the effect of inquiry learning strategies on students learning outcomes. Learning models are one of the important things to apply in improving student learning outcomes. The inquiry learning model requires students to contribute actively during teaching and learning activities, both intellectually, emotionally and physically, with the hope that students will be able to strive for self-development, respond, provide opinions and solve learning problems both in groups and individually. This research is motivated by the problem of low student learning outcomes. Learning outcomes are a process characterized by changes in a person. Changes as a result of the learning process can be shown in various forms such as changes in skills, abilities, habits, as well as changes in aspects at the end of a lesson. Student learning outcomes are seen from ability, understanding and evaluation. These abilities cover cognitive, affective and psychomotor aspects. If these three aspects are owned or mastered by students, then the student's learning outcomes will be visible.